Zero-Based Grading System and Academic Performance among Quezon City University Students (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The researchers analysed the student attitudes towards the Zero-Based Grading System (ZBGS) at Quezon City University and its effect on student academic performance. A descriptive quantitative approach was selected for the study. A total of 407 student participants completed a survey containing items regarding demographic profile, awareness of grading policies, understanding of criteria for academic outputs, perception of fairness in assessment, and impact on academic discipline. Data gathered revealed that the majority of participants were third-year students, from the College of Computer Studies and College of Engineering, with GWA values being in the range of either very good to good range, and a majority of the respondents had experienced ZBGS for one or two semesters. The study found that the majority of the respondents were aware of the grading policies which yielded the highest weighted mean. Moreover, the results of the analyses indicated that statistically significant differences in ZBGS assessments occurred based on year level and GWA of the respondents but not according to College/Department or length of time exposure in ZBGS. Furthermore, the correlation analysis revealed a significant relationship between ZBGS assessment and academic performance, indicating that more favorable perceptions of ZBGS were associated with better GWA. Overall, the results of this study provided evidence that students generally accepted ZBGS as a reasonable grading practice and that more favorable perceptions of the system were associated with better academic performance, supporting the clear and consistent implementation of grading policies.